PENERAPAN METODE KLASTERISASI K-MEANS UNTUK STRATEGI PROMOSI PADA SMK TAMANSISWA SUKADAMAI - Teti Purwanti; William Ramdhan; Santoso Santoso (LPPM STMIK Royal Kisaran, 2021)
Abstract: SMK Tamansiswa Sukadamai is one of the private schools in Pulo Bandring District which annually admits new students, this will affect the amount of student data that goes up and down. So far, SMK Tamansiswa Sukadamai has implemented a promotional strategy but it is still not optimal because the number of students registered at SMK Tamansiswa Sukadamai is more dominant in certain areas. Based on this, we need a technique that is able to assist in transforming the data into useful information, namely by applying data mining for promotional strategies, which can be the basis or guideline for promotional strategies based on areas where there are not many students present. The application of the k-means clustering method for promotional strategies can assist in the data grouping process in the form of data grouping results for C1